Trade and wage inequality: The mediating roles of occupations in Germany - Reichelt, Malte; Malik, Samreen; Suesse, Marvin (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
Recent evidence shows that rising wage inequality in industrialized countries can partially be attributed to trade integration. However, it is unclear what the mechanisms behind this relationship are. Previous explanations pointed toward the displacement of mid-wage manufacturing workers as a response to rising imports. However, for Germany it has been shown that rising exports likewise create manufacturing jobs, indicating that industry-based explanations fall short. We argue that focusing on changes of the occupational composition, as well as changes in the occupation-specific median and top wages, may help to explain the effects of trade on inequality. We draw on a task-based approach, theories of power relations between occupations, as well as self-selection by firms to arrive at predictions about the mediating role of occupations. We analyze German trade relations with China between 1994 and 2010 using social security data (BHP, IEB) and data on international trade flows (COMTRADE). Applying an instrumental variable approach, we find that, surprisingly, imports do not affect wage inequality. Instead, rising exports to China are responsible for the effects of trade integration on inequality as they increase wage dispersion within German labor market regions. Although increased trade integration alters the occupational task composition, we find no evidence that these shifts mediate the effects of exports on wage inequality. Instead, exports increase the wages of some occupations, especially for top earners, highlighting the importance of focusing on within-occupation dynamic